A Multilevel Physical Activity Intervention Among Chinese Rural Older Adults (Stay Active While Aging): A Study Protocol for a Clustered Randomized Controlled Trial - Nanyan Li; Yufei Wang; Qian Deng; Julinling Hu; Junmin Zhou (Frontiers Media S.A., 2022)
BackgroundAlthough a large number of studies have confirmed the benefits of physical activity (PA) in preventing age-related diseases and disabilities, a growing number of older people spent more time in sedentary behavior as opposed to PA. To reverse the alarming trend, numerous studies have corroborated the effectiveness of PA interventions in improving PA among older adults. However, such research is scarce in rural China, where a majority of older adults do not meet the PA recommendation. The Stay Active While Aging (SAWA) aimed to conduct an intervention to improve the PA level among older adults in rural China.MethodsThe SAWA is designed as a single-blind, clustered randomized controlled trial carried out in rural Sichuan, China with an 8-week intervention and a 24-month follow-up. The intervention group will receive a multilevel intervention (individual, interpersonal, and community levels), while the control group will not. The primary outcome is the PA level. Secondary outcome measures include sedentary behavior level, self-efficacy, self-regulation, cognitive function, night-time sleep quality, and anthropometry. The difference-in-differences (DID) will be performed to investigate the between-group differences, adjusted for baseline data and covariates.DiscussionThe SAWA trial will provide a multilevel intervention based on the socio-ecologic model among older adults in rural China. We target the PA level and health status changes while also focus on the maintenance of such intervention during 24 months. If the SAWA produces positive results, it will be possible to recommend similar strategies to be implemented in other Chinese older adults and beyond.Trial registrationChiCTR2100045653 (https://www.chictr.org.cn/index.aspx).